The role of tenascin-C in tumor microenvironments and its potential as a therapeutic target - Wang, Yaran; Wen, Xiaohui; Su, Chao; You, Yanyi; Jiang, Ziqing; Fan, Qin; Zhu, Daoqi (Frontiers in Cell and Developmental Biology, 2025)
The tumor microenvironment (TME) plays a pivotal role in cancer development and progression, and comprises various cellular and non-cellular components that interact with tumor cells. Tenascin-C (TNC) is an extracellular matrix glycoprotein that is widely expressed in the cancer stroma and influences critical processes, such as cell adhesion, migration, and immune modulation. This review examines the multifaceted roles of TNC in different TMEs, including the mechanical, immune, and metabolic microenvironments, as well as the radiation microenvironment (RME). In the context of the mechanical microenvironment, TNC actively participates in extracellular matrix remodeling, thereby facilitating tumor invasion. Notably, TNC exhibits immunosuppressive effects on T cells and promotes the recruitment of immunosuppressive cells within the immune microenvironment. Furthermore, TNC is implicated in the tumor hypoxia response, glucose metabolism reprogramming, and regulation of pH balance, underscoring its role in the metabolic microenvironment. Intriguingly, TNC also influences radiosensitivity within RME. This review also explores the potential of TNC as a biomarker for cancer prognosis and as a target for therapeutic interventions. By integrating recent advances in single-cell sequencing and spatial omics, we propose innovative strategies for leveraging TNC in personalized cancer therapy. Future research directions are discussed, focusing on distinct isoforms of TNC, their interaction networks, and their roles in radiotherapy efficacy. This comprehensive analysis underscores the importance of TNC in understanding tumor dynamics and improving cancer treatment outcomes.